2020
DOI: 10.1002/agj2.20145
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to Fusarium verticillioides infection and fumonisin accumulation in maize F1 hybrids and subsequent F2 populations

Abstract: Fusarium verticillioides causes Fusarium ear rot (FER) in maize (Zea mays L.), thus reducing grain quality, yield, and contaminates grains with fumonisins. Grain infection by these fungi occurs before harvest and selection of parental lines resistant to fumonisin accumulation for breeding purposes is the most effective and environmentally friendly control strategy for F. verticillioides. This study intended to evaluate F1 hybrids and F2 breeding populations in Kenya for improved resistance to FER and fumonisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…In terms of gene effects, this was similar to the findings by Ouko et al. (2020) who found additive and nonadditive gene effects to be almost equally important for resistance to fumonisins. There was a contradiction in terms of maternal effects, as they found no significant maternal effects.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In terms of gene effects, this was similar to the findings by Ouko et al. (2020) who found additive and nonadditive gene effects to be almost equally important for resistance to fumonisins. There was a contradiction in terms of maternal effects, as they found no significant maternal effects.…”
Section: Discussionsupporting
confidence: 90%
“…Ouko et al. (2020) found both nonadditive and additive gene effects playing a significant role in the inheritance of resistance to aflatoxins caused by A. flavus . Walker and White (2001) attributed resistance to A. flavus infection to additive gene effects, while nonadditive gene effects were associated with resistance to aflatoxin production.…”
Section: Introductionmentioning
confidence: 99%
“…If the GCA effect is significant but the SCA effect is not, only GCA can predict offspring performance (Gilbert, 1958). Some studies have indicated that FER resistance is promoted by dominant effects (Clements et al., 2004), whereas others have indicated that it results from a combination of additive and dominant effects (Hung & Holland, 2012; Nankam & Pataky, 1996; Ouko et al., 2020; Tembo et al., 2022). Given that previous studies have shown no significant maternal effects in the inheritance of FER resistance (Netshifhefhe et al., 2018; Pereira et al., 2017; Schwantes et al., 2017), we performed a genetic analysis using half‐diallel crosses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results have indicated a moderate to high correlation between inbred lines and their hybrids (Butoto et al, 2021;Löffler et al, 2011;Ouko et al, 2020). If both parents have high resistance, their hybrid will exhibit high resistance; conversely, if both parents are highly susceptible, their hybrid will also likely be highly susceptible.…”
Section: Crop Sciencementioning
confidence: 98%
See 1 more Smart Citation